Matching user needs to technology in dementia care: experiences with the Alma Supervisor Educational Program - Holthe, Torhild; Wulff-Jacobsen, Ida (Family Medicine & Primary Care Review, 2016)
The number of individuals with dementia in Norway is more than 78,000, and, as in all other European countries, this figure is expected to rise over the coming decades. The Norwegian Health Directorate encourages municipalities to make use of ‘welfare technology’ in order to contribute to independent living and quality of life in older adults, to increase the quality of community health care, to save time when providing community health services and to reduce costs, e.g. admission to a nursing home. Introducing welfare technology to care recipients requires innovation on the part of the community health care service with regard to increasing the competency of the staff in the operation of the technologies, as well as in establishing an infrastructure for ‘digital communication’. Research has shown that access to assistive technology may support individuals with mild cognitive impairments, as well as in an early phase of dementia. However, it is crucial that the technology addresses an identified need, and that the device is tailored to the person’s preferences and context. Therefore, it is important to train health professionals to assess the user’s needs and preferences and to identify resources and limitations in the particular context. Alma’s House in Oslo is a demonstration site and education center for welfare technologies. The education program for the certification of Alma supervisors has become an important strategy in educating occupational therapists (OTs) and nurses on how to assess user needs, identify appropriate technology and implement this into the care recipient’s home.